Framework for Gender, Diversity and Inclusion in CGIAR’s Workplaces - CGIAR System Organization (CGIAR System Organization, 2020)
CGIAR’s workplaces are enabling and inclusive. Diversity in all its dimensions is embraced and every person is supported to reach their full potential, so as to drive the engagement and innovation needed for a world free of poverty, hunger and environmental degradation.